SURFACE SOLAR RADIATION IN A TROPICAL AREA ESTIMATED FROM DIFFERENT MODELS - Pavão, Vagner Marques; Biurdes, Marcelo Sacardi; Querino, Carlos Alexandre Santos; Machado, Nadja Gomes; Pavão, Larissa Leite; Silva, Pablinne Cynthia Batista da Silva e (Revista Brasileira de Climatologia, 2021)
The Global Solar Radiation (Rg) is considered the main power that regulates the biophysical processes in the surface-atmosphere interface. Many regions of the Earth do not have those kinds of measures available, consequently approach models that allow confident estimates are necessary. Thus, the objective of this article was to evaluate the performance of the models proposed by Angström-Prescost (1940), Hay (1979) and Bristow & Campbell (1984) to estimate the solar global radiation in the city of Sinop, Mato Grosso state. Therefore, data from the National Institute of Meteorology (INMET), from 2006 to 2012, have been used to validate and parameterize the models. Solar Global Radiation (Rg), air temperature (maxima and minima), clarity atmospheric index (kt) and the relative sunshine duration (Ir) have shown seasonality under influence of the cloudiness. All the three models have estimated Rg satisfactorily with Pearson’s correlation coefficient classified as strong. Nevertheless, Hay’s model has presented the lowest errors and coefficients lightly better than the others models. However, all the models have presented similar results, which make them applicable to the region. Our results still suggest that further research, such as use of the models to the entire region of Mato Grosso state, is necessary to improve the estimate models of Rg in that area.